Formulasi Pemanfaatan Ekstrak Daun Pepaya (Carica papaya L.) Sebagai Pestisida Nabati: Papaya Leaf Extract Utilization Formulation (Carica papaya L.) as a Pesticide Vegetable - Sukmawati Sukmawati; Ameliawati Ameliawati (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2024)
Background: Many people do not understand how to use synthetic pesticides so that they can be harmful to humans. The use of pesticides made from nature can be a solution for the community, not only materials that are easily available but also ingredients that are safer because they use natural ingredients. Papaya leaves (Carica papaya L.) contain saponin and flavonoid compounds where these compounds can cause the death of pests.  Aim: This study aims to formulate it in pesticide preparations and then evaluate it so that it can be seen that the concentration of pesticide preparations is good  Method: This type of research is experimental in the laboratory by making 3 formulas consisting of F1 with a concentration of 8% papaya leaf extract, F2 12% and F3 16%. The tests include organoleptic, homogeneity and pH. Result: The results showed that the organoleptic tests carried out on all formulations did not have much difference, starting from the smell and shape they both had a liquid form, a distinctive smell of papaya leaves, only the concentrations from small to large experienced a brown to greenish-brown color. The homogeneity test results from the three formulations were not homogeneous and the pH test results were the more extracts, the higher the pH value. Conclusion:. Papaya leaf extract with concentrations of 8%, 12%, and 16% can be formulated in the form of pesticide preparations. Keywords: Excessive Synthetic Pesticides, Papaya Leaves (Carica papaya L.), Pesticides, Pests